2011
DOI: 10.1073/pnas.1104598108
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial chemotaxis modulates host cell apoptosis to establish a T-helper cell, type 17 (Th17)-dominant immune response in Helicobacter pylori infection

Abstract: The host inflammatory response to chronic bacterial infections often dictates the disease outcome. In the case of the gastric pathogen Helicobacter pylori, host inflammatory responses result in outcomes that range from moderate and asymptomatic to more severe with concomitant ulcer or cancers. It was found recently that H. pylori chemotaxis mutants (Che − ), which lack directed motility but colonize to nearly wild-type levels, trigger less host inflammation. We used these mutants to observe host immune respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 36 publications
0
46
0
Order By: Relevance
“…All of these stimuli very likely influence bacterial energy metabolism and would need to be balanced continuously by the TlpD-mediated bacterial behavior to locally optimize bacterial distribution and persistence. H. pylori colonization provokes a gastric inflammatory and oxidative stress response, and this response is increased for cagPAI-positive strains, mainly by the direct interaction of the bacteria with the gastric epithelium, as has been observed in humans, mice, and gerbils (1,36,51,(70)(71)(72)(73). Our in vitro assays using paraquat suggested an intrinsically reduced fitness of the tlpD mutants in the presence of oxidative stress, which was partially reverted by TlpD complementation.…”
Section: Discussionmentioning
confidence: 81%
“…All of these stimuli very likely influence bacterial energy metabolism and would need to be balanced continuously by the TlpD-mediated bacterial behavior to locally optimize bacterial distribution and persistence. H. pylori colonization provokes a gastric inflammatory and oxidative stress response, and this response is increased for cagPAI-positive strains, mainly by the direct interaction of the bacteria with the gastric epithelium, as has been observed in humans, mice, and gerbils (1,36,51,(70)(71)(72)(73). Our in vitro assays using paraquat suggested an intrinsically reduced fitness of the tlpD mutants in the presence of oxidative stress, which was partially reverted by TlpD complementation.…”
Section: Discussionmentioning
confidence: 81%
“…Such species remain to be discovered, however. It is tempting to speculate that the reduced inflammatory response we observe early postinoculation would drive conditions that would result in reduced inflammation long term; other work has demonstrated that the CD4 response at 4 weeks accurately reflects the long-term H. pylori inflammatory response (26). However, future experiments will need to examine the enduring effects on the inflammatory state.…”
Section: Discussionmentioning
confidence: 99%
“…3B and C). We chose these cells as they are known to arrive relatively early in response to H. pylori infection and also are reflective of the host response at later time points (26,35). As expected, normal mice developed a CD4 ϩ response to H. pylori infection that was significantly above that of uninfected mice (Fig.…”
Section: (21) Gastric Tissue Was From Mice From Either Charles Rivermentioning
confidence: 97%
“…It has recently been shown that Th17 cells and IL-17 function during infections to eliminate pathogens such as Helicobacter pylori, Mycobacterium tuberculosis and Toxoplasma, etc. [7,8] . The number and activation of CD4+ T cells, and especially Th17 cells, may adversely impact the cytokine network and a patient's recovery from pneumococcal pneumonia, as well as their ability to eliminate streptococci [9,10] .…”
Section: Association Of Pneumococcal Carriage and Expression Of Foxp3mentioning
confidence: 99%